The effect of the progressive inquiry model on creative thinking and learning to perform the smash and court defense skills in volleyball for students - Al-Aboudi , Fatima (Journal of Physical Education, 2025)
The aim of the research was to prepare educational exercises and employ them using the progressive inquiry model to learn to perform the skills of smashing and defending the court in volleyball for students, and to identify the effect of the progressive inquiry model on creative thinking and learning to perform the skills of smashing and defending the court in volleyball for students. The experimental research method was adopted by designing two equal experimental and control groups with tight control in the pre- and post-tests. The limits of the community of this problem were represented by the fifth-grade preparatory students from the (1 June) Secondary School for Boys for the academic year (2024/2025), numbering (99) students, from whom (66) students were chosen for the research sample, representing (66.667%) of their original community. Then, students from the experimental group and the other control group were chosen from them in equal numbers. (20) students were chosen for the sample of the scientific foundations of the creative thinking test, representing (20.202%) of their original community. The remaining (13) students were also chosen for the exploratory experiment sample, representing (13%) of their original community. (13.131%) of their original community, and after determining the tests of the three dependent variables and completing the preparation of the educational exercises and employing them with the progressive inquiry model, the pre-tests were applied as a start to the research experiment, and then applying the vocabulary of the educational exercises with the progressive inquiry model in practical physical education lessons to the students of the experimental group, while the students of the control group apply the method followed as it is in their practical lessons, and completing this experiment by applying the post-tests, and processing the results by means of the (SPSS) system to be the conclusions and recommendations that preparing educational exercises with the progressive inquiry model in the educational units of practical volleyball lessons is suitable for fifth-grade middle school students, and that applying them in the educational units of practical volleyball lessons helps improve the level of creative thinking and helps in learning to perform the skills of smashing and defending the court in volleyball for students who learn with it, and with superiority over students who learn without it, and it is necessary when preparing educational exercises with the progressive inquiry model to give (2) minutes before performing each exercise from them to enable students to investigate and improve creative thinking in the educational units to learn skill performance With volleyball.